2019
DOI: 10.5194/acp-19-15503-2019
|View full text |Cite
|
Sign up to set email alerts
|

Complex refractive indices and single-scattering albedo of global dust aerosols in the shortwave spectrum and relationship to size and iron content

Abstract: Abstract. The optical properties of airborne mineral dust depend on its mineralogy, size distribution, and shape, and they might vary between different source regions. To date, large differences in refractive index values found in the literature have not been fully explained. In this paper we present a new dataset of complex refractive indices (m=n-ik) and single-scattering albedos (SSAs) for 19 mineral dust aerosols over the 370–950 nm range in dry conditions. Dust aerosols were generated from natural parent … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
198
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 162 publications
(234 citation statements)
references
References 118 publications
(203 reference statements)
32
198
3
1
Order By: Relevance
“…The Arctic sample ( Figure 3f) has a much higher iron contribution to the single particles, potentially related to the different weathering regime and geological basement. While the total iron content optical properties cannot be derived directly with high accuracy due to the varying contribution of structural iron [51,65], it was shown that estimates of the imaginary part of the refractive index obtained from composition measurements agree reasonably well with optical measurements [6,51]. For the size range of 4-20 µm (transported cross-section maximum), the total deposited aerosol imaginary part of the refractive index for 470 nm wavelength k 470 is 0.4 × 10 −3 at Tenerife and (0.6-0.7) × 10 −3 at all other locations except for Svalbard, where it is 0.9 × 10 −3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Arctic sample ( Figure 3f) has a much higher iron contribution to the single particles, potentially related to the different weathering regime and geological basement. While the total iron content optical properties cannot be derived directly with high accuracy due to the varying contribution of structural iron [51,65], it was shown that estimates of the imaginary part of the refractive index obtained from composition measurements agree reasonably well with optical measurements [6,51]. For the size range of 4-20 µm (transported cross-section maximum), the total deposited aerosol imaginary part of the refractive index for 470 nm wavelength k 470 is 0.4 × 10 −3 at Tenerife and (0.6-0.7) × 10 −3 at all other locations except for Svalbard, where it is 0.9 × 10 −3 .…”
Section: Resultsmentioning
confidence: 99%
“…For |Fe| > 0.2, only the Fe index is used as a classification criterion, whereas for |Fe| < 0.2, an additional condition is used for ruling out the classification of particles dominated by non-silicate components ( Mg + |Al| + |Si| + |P| + |Fe| > 0.3), for which this approach would lead to high uncertainty. In addition, from the iron content of the single particles, the imaginary part of the index of refraction at 470 nm wavelength (k 470 ) is estimated following an empirical approach from Di Biagio et al [51], who established a relationship between the iron content and the optical properties. To estimate the single particle iron content, the dust compounds Na, Mg, Al, Si, P, K, Ti, and Fe are assumed to exist in their oxidized form.…”
Section: Class Name Conditions For Being Positively Classifiedmentioning
confidence: 99%
“…As illustrated by the most recent laboratory measurements of the dust refractive index by Di Biagio et al (2019), dust shortwave absorbability is closely related to the mass concentration of iron oxides (FeOx), and the imaginary part of the dust refractive index can be empirically inferred given the mass concentration of FeOx by a formula. In this study, mass concentrations of 1.2%, 2.4%, and 4.8% FeOx values are used, where 2.4% is the global mean value in the measurements of Di Biagio et al (2019).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the uncertainties stemming from the theoretical and experimental methods for obtaining the refractive indices, the mineral composition variability from different dust source regions significantly impacts the imaginary parts of the complex refractive indices (Balkanski et al, 2007; Sokolik & Toon, 1999), which are mainly determined by the iron oxide content (shortwave) and clay, quartz, and calcium‐rich components (longwave). For example, Di Biagio et al (2019) reveal the close relationship between iron oxides (FeOx) in mineral composition and the imaginary parts of the dust refractive indices in shortwave bands; most importantly, their results show that the imaginary parts of dust refractive indices were overestimated in previous literature (e.g., Hess et al, 1998; Shettle & Fenn, 1979). This lower dust absorption finding is consistent with some other studies (e.g., Balkanski et al, 2007; Kim et al, 2011).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation